Perinatal Genetic Screening From the Perspective of India-Born Individuals and Healthcare Providers in Victoria, Australia: A Community-Engaged Grounded Theory Protocol - Anaita Kanga-Parabia; Laura J. Biggs; Belinda Dawson-McClaren; Sharon Lewis; Karamdeep K. Pangli; Alison D. Archibald (International Journal of Qualitative Methods)
Advances in genomic technologies are providing people with access to earlier diagnoses, intervention, and treatment of genetic conditions. However, there are inequities in access to and experiences of genomic technologies for several communities, such as people from non-European backgrounds and people who are born outside the country in which they reside. It is crucial to understand whether and how these issues manifest in different genomic healthcare settings across the world to develop targeted interventions and ultimately reduce healthcare inequities. In this research, we aim to specifically understand the process of perinatal genetic screening in Victoria, Australia from the perspective of people born in India and relevant healthcare providers. In this protocol, we provide a practical example of how community engagement can be used to extend grounded theory methodology in the genomic healthcare context. We are using grounded theory methodology because it provides a systematic approach to explain a complex process in the context of limited existing research. Furthermore, we are engaging community and healthcare providers throughout the research process. All community methods are being conducted in English, Punjabi and Hindi languages. Potential participants are being invited to participate via community networks, professional networks, relevant organisations, social media, and snowballing. The research team are able to address any questions and support participants through the consent process. Participants may share their views via an interview or qualitative survey. Recruitment, data generation, and analysis are occurring concurrently, and will result in a grounded theory explaining the process of perinatal genetic screening. The theory will inform equitable delivery of perinatal genetic screening in Australia as well as future research with other communities facing inequities in genomic healthcare.